Power market design beyond 2020: Time to revisit key elements? - Karsten Neuhoff; Sophia Ruester; Sebastian Schwenen (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We revisit key elements of European power market design with respect to both short term operation and longer-term investment and re-investment choices. For short term markets, the European policy debate focuses on the definition of common interfaces, like for example gate closure time. We argue that that this is insufficient if the market design is to accommodate for the different needs of renewable and conventional generation assets and different flexibility options. The market design needs to ensure resources are pooled over larger geographic areas, the full flexibility of different assets can be realized with complex bids and scarce network resources are efficiently used. For investment and re-investment choices we argue that different technology groups like wind and solar versus fossil fuel based generation may warrant different treatment - reflecting different level of publicly accessible information, requirements for grid infrastructure, types of strategic choices relevant for the sector and share of capital cost in overall generation costs. We discuss opportunities for such a differentiated treatment and implications for electricity consumers.
Keywords: L11; L94; G32; 330; power market design; regulation; investment framework